Novel Biomaterial for Artery Patch in Swine Model With High-Fat Diet - Lu, Xiao; Han, Ling; Guo, Xiaomei; Wang, Mengjun; Baradarian, Sam; Golts, Eugene; Kassab, Ghassan S. (Frontiers in Bioengineering and Biotechnology, 2021)
Objective: We evaluated swine and bovine pulmonary visceral pleura in artery patch-angioplasty in swine model of high fat diet. Background: Arterial patch-angioplasty are frequently used for repair or reconstruction of arteries. Autologous patch is often limited by number and dimension of donor tissue and can result in donor complications. It is known that mechanical mismatch is a cause of poor performance of vascular reconstruction. Hence, there is significant need for alternative patch biomaterials with similar compliance as native arteries. Methods: The pulmonary visceral pleura (PVP) was peeled from swine and bovine lungs with aid of hydrostatic pressure. The swine and bovine PVPs were crosslinked with glutaraldehyde and sterilized. The swine PVP (sPVP) patches were implanted in carotid and femoral arteries of six Yorkshire pigs that were fed regular diet and euthanized at 2 and 4 months postoperative. The bovine PVP (bPVP) patches were implanted in carotid artery of six Yucatan pigs that were fed high-fat diet and euthanized at 4 months postoperative. Patency was evaluated by ultrasound and angiography. Neo-endothelium and media were evaluated by histologic examination. Results: All arteries in patch-angioplasties remained patent with no adhesions, inflammation, or aneurysms. The biomarkers of endothelial cells (e.g., Factor VIII and eNOS) were detected in the neo-endothelial cells. We observed the endothelial cell-cell junctions in the confluent neo-endothelium in the PVP patches. Neo-media composited of vascular smooth muscle developed similar to native arteries. In the hypercholesterolemic model, we observed accumulation of cholesterol in arterial tissues and in neo-vascular tissues in the PVP patches. The protein expressions related to lipid transport and metabolism (e.g., APOE-1, ABCA, and PACK9) were observed in arterial and neo-vascular tissues. Conclusions: The PVP patch-angioplasty overcomes the pitfalls of compliance mismatch of synthetic patches and has a non-thrombogenic surface. The proliferation of vascular cells assembled the neo-endothelium and media in the patch patch-angioplasties to support long-term patency. The neo-vascular tissue in PVP patch-angioplasty develops similar cellular functions for lipid transport and metabolism as native arteries in hypercholesterolemia.